Tinjauan Yuridis Terhadap Putusan Bebas Pelaku Pemerkosaan Anak di Lubuk Basung - Amiratul Aulia Hanifah; Syarah Zafira Keisua; Annisa Kharen Pricilla; Sherlytta Ananova; Ahmad Feisal Abi Hanif; Naufal Febriansyah; Warih Ayu Indah Kusumo; Alsa Mustafa Malawati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
J.E. Sahetapy argued that crime is a product of culture, evolving to become more modern and complex. Children, as future leaders, require guaranteed rights and protection as regulated in Indonesia's laws, including the Criminal Code and the Child Protection Law. However, violations like sexual violence by those closest to them, such as parents, persist. This research examines cases of sexual violence against children by biological parents, focusing on Supreme Court decisions. Using normative juridical methods and a statutory approach, the study analyzes the legal aspects of these cases. Findings reveal that despite evidence, defendants were acquitted due to the judge's doubts about witness statements and existing evidence, applying the in dubio pro reo principle. This decision has sparked debate for potentially setting a harmful precedent and hindering child protection enforcement. The study underscores the need for more responsive and appropriate legal implementation to achieve justice and optimal protection for child victims of sexual violence.